2020
DOI: 10.1039/c9ra10325b
|View full text |Cite
|
Sign up to set email alerts
|

The substitution of a single amino acid with its enantiomer for control over the adjuvant activity of self-assembling peptides

Abstract: The substitution of a single amino acid with its enantiomer in Nap-GFFY conferred different self-assembly performances and distinct adjuvant activities on the corresponding peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Our choice of heterochiral sequences was dictated by the observation that introducing d -amino acids at selected positions has proven successful as a strategy to achieve hydrogels from uncapped tripeptides. , In this manner, it is possible to orient favorably the side chains of hydrophobic sequences to access amphiphilic gelling structures, as was recently reviewed . Heterochirality is gaining momentum as a strategy to tailor peptide self-assembly. Uncapped dipeptides are very attractive building blocks due to their chemical simplicity. Furthermore, enantiomers are expected to display the same self-assembly behavior in achiral environments, therefore, investigation of compounds 2 – 6 will shed light also on the self-assembly of their mirror-image l - d dipeptide isomers.…”
mentioning
confidence: 99%
“…Our choice of heterochiral sequences was dictated by the observation that introducing d -amino acids at selected positions has proven successful as a strategy to achieve hydrogels from uncapped tripeptides. , In this manner, it is possible to orient favorably the side chains of hydrophobic sequences to access amphiphilic gelling structures, as was recently reviewed . Heterochirality is gaining momentum as a strategy to tailor peptide self-assembly. Uncapped dipeptides are very attractive building blocks due to their chemical simplicity. Furthermore, enantiomers are expected to display the same self-assembly behavior in achiral environments, therefore, investigation of compounds 2 – 6 will shed light also on the self-assembly of their mirror-image l - d dipeptide isomers.…”
mentioning
confidence: 99%
“…The sequence of the Nap-GFFY peptide was deemed necessary as a study substituting and/or changing the position of the amino acids concluded that both the position of each amino acid and the number of aromatic amino acids were deemed necessary in determining the potency of the adjuvant. [130,131] The absence of any amino acid in the Nap-GFFY hydrogel sequence was shown to cause a 10x reduction in the antibody titer after OVA vaccination in C57BL/6 mice, highlighting the importance of choosing specific amino acids in peptide bioconjugates that form hydrogels. It was found that if the phenylalanine amino acids were substituted with Gly, the compounds did not self-assemble, showing the importance of the aromatic amino acids in hydrogel formation.…”
Section: Hydrogel Propertiesmentioning
confidence: 99%
“…Based on the pure chiral hydrogel Nap-GFFY ( l -gel) containing three transformable chiral amino acid sites, Li et al 82 replaced l -amino acids with d -amino acids and obtained three heterarchical hydrogels, Nap-G D FFY (gel-1), Nap-GF D FY (gel-2), and Nap-GFF D Y (gel-3). The four kinds of hydrogels have differences in their gelation temperatures and the minimum gelation concentration.…”
Section: Factors Influencing the Formation Of Peptide Hydrogelsmentioning
confidence: 99%